2018
DOI: 10.3889/oamjms.2018.092
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Parameters as Predictors of Response to Cardiac Resynchronization Therapy

Abstract: INTRODUCTION:Although strict selection criteria are used to select patients for cardiac resynchronisation therapy, up to 30% of patients do not have a positive clinical response.PATIENTS:A total of 102 consecutive patients who had biventricular pacemaker/defibrillator (CRT-P or CRT-D) implanted were enrolled in this prospective observational study.RESULTS:During the average follow-up period of 24.3 months 5 patients died and 17 (16.7%) patients were hospitalised with the symptoms of heart failure; 75 (73.5%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A simultaneous delay in the activation of the right ventricle (for example because of a right ventricular pressure overload and enlargement), or posterosuperiorly pointing to late left ventricular activation because of biventricular enlargement [39], or an apical location of a branch of the left posterior fascicle [40], are suspected. Poposka et al [41] also found that a larger R/S amplitude ratio in V6 is a predictor of CRT response in both LBBB and non-LBBB patients. Another similar marker which may predict CRT response in LBBB is the lead one ratio (LOR) [42].…”
Section: S-wavesmentioning
confidence: 92%
“…A simultaneous delay in the activation of the right ventricle (for example because of a right ventricular pressure overload and enlargement), or posterosuperiorly pointing to late left ventricular activation because of biventricular enlargement [39], or an apical location of a branch of the left posterior fascicle [40], are suspected. Poposka et al [41] also found that a larger R/S amplitude ratio in V6 is a predictor of CRT response in both LBBB and non-LBBB patients. Another similar marker which may predict CRT response in LBBB is the lead one ratio (LOR) [42].…”
Section: S-wavesmentioning
confidence: 92%
“…While no single ECG parameter could predict CRT response on its own, yet specific parameters did demonstrate a difference between responders and nonresponders. In particular, an increased amplitude of the R wave in lead V6, an elevated R/S ratio in the same lead, and the derived figure (S1 + R6) − (S6 + R1) may suggest a greater likelihood of response in both LBBB and non-LBBB patients [67].…”
Section: Electrocardiographic Parameters As Predictors Of Response To...mentioning
confidence: 94%
“…LBBB vs. Non-LBBB Patients: Patients with LBBB typically have a more dyssynchronous contraction pattern, and CRT aims to correct this dyssynchrony. Therefore, parameters that reflect the extent of dyssynchrony in LBBB patients may be more predictive of CRT response in this group compared to non-LBBB patients (Figure 12) [67,71].…”
Section: Height Of R Wave In V6mentioning
confidence: 99%
“…The R6/S6 ratio tended to be higher, but it did not reach a statistical significance (Poposka et al, 2018). Bear et al evaluated the sensitivity of body surface mapping and ECG imaging to detect electrical dyssynchrony noninvasively, and experimentally using Langendorff isolated perfused in pig hearts with LBBB induced through ablation.…”
Section: ) Studies Have Identified Subpopulations Of Non-lbbb Patientsmentioning
confidence: 99%